2008
DOI: 10.1002/srin.200806137
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of the Steel/Slag Interface in a Continuous Casting Tundish

Abstract: It is very important to understand the underlying physical phenomena at the steel/slag interface in a continuous casting tundish in order to control reoxidation and deoxidation phenomena that can occur. Aiming to investigate probable sources of exogenous inclusions originating from the covering slag, an existing mathematical model of the tundish was augmented to include key physical parameters needed for the prediction of the physical behaviour of steel/slag mixing phenomena. Results showed a recirculation flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 12 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…The temperature‐dependent dynamic viscosity for steel, ν st , is calculated according to Kawai and Shiraishi 43. The temperature‐dependent dynamic viscosity for pure slag, ν sl , is calculated according to Seetharaman et al44 The slag/steel mixing properties and the dispersed slag phase droplet size are calculated according to Solhed et al45…”
Section: Model Descriptionmentioning
confidence: 99%
“…The temperature‐dependent dynamic viscosity for steel, ν st , is calculated according to Kawai and Shiraishi 43. The temperature‐dependent dynamic viscosity for pure slag, ν sl , is calculated according to Seetharaman et al44 The slag/steel mixing properties and the dispersed slag phase droplet size are calculated according to Solhed et al45…”
Section: Model Descriptionmentioning
confidence: 99%
“…However, much less attention has been paid to the reduction stage. Although numerous studies have been conducted on the emulsification of slag [31][32][33][34][35][36][37][38][39][40][41][42] and reduction of slag 18,[43][44][45][46] as separate research fields, a phenomena-based model capable of combining the present knowledge of both phenomena has not been previously discussed in the literature.…”
Section: Review Of the Existing Modelsmentioning
confidence: 99%
“…Simulated slag droplet diameters for tundish are typically smaller than 1 mm. 19) Many physical water-experiments have also been reported in the literature. 16,17,[20][21][22] Frohberg et al 20) reported mean diameters ranging from 2.3 to 2.8 mm, while Savolainen et al 22) observed average droplet sizes in the range of 2.0 to 8.5 mm.…”
Section: )mentioning
confidence: 99%